2004
DOI: 10.1577/t03-033.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freshwater and Marine Growth Rates on Early Maturity in Male Coho and Chinook Salmon

Abstract: In many populations of salmonid fishes, a fraction of the males mature at a younger age than the females; these males are termed jacks if they have migrated to sea and precocious parr if they matured in freshwater. We examined detailed data on the University of Washington hatchery populations of coho salmon Oncorhynchus kisutch and Chinook salmon O. tshawytscha for more than 30 years to test whether rapid growth in freshwater or at sea increases the probability of early maturity in males. The average size of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 46 publications
11
80
1
Order By: Relevance
“…The smallest of these fish was 61.3 g and 189 mm, which is larger than the size at which most normal coho salmon undergo the smolting process (average of typically ,25 g) found at this time of year (Vo¨llestad et al 2004). The largest of the transgenic fish was 238 g and measured 278 mm.…”
Section: Resultsmentioning
confidence: 78%
“…The smallest of these fish was 61.3 g and 189 mm, which is larger than the size at which most normal coho salmon undergo the smolting process (average of typically ,25 g) found at this time of year (Vo¨llestad et al 2004). The largest of the transgenic fish was 238 g and measured 278 mm.…”
Section: Resultsmentioning
confidence: 78%
“…Additionally, fall run Chinook salmon held for extended rearing peri-ods and released the following fall, as "yearlings" tend to mature later than earlier releases (Hankin 1990). Among wild salmon, however, size at ocean entry is negatively correlated with age at maturity (e.g., Vøllestad et al 2004), and so yearling releases (of larger fish) may not delay maturity in all cases, although timing effects may predominate over the effects of size at release.…”
Section: Maturation Schedulementioning
confidence: 99%
“…Evidence for strong heritability in age-at-maturity comes from quantitative genetic studies (Hankin et al 1993;Heath et al 1994;Heat et al 2002) and measures at the population level (Hard et al 1985, Appleby et al 2003. Physiological traits mediated by environmental conditions (e.g., body size, fatness), can trigger early male maturation (Vøllestad et al 2004;Shearer et al 2008). Early male maturation may represent the default developmental pathway, with the slower growing males repressing maturation until the following year (Aubin-Horth 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this study the effects of two environmental factors, photoperiod (at emergence) and food availability (growth during early rearing), on seasonal timing of smolting, smolt quality, and age of male maturity are being examined in spring Chinook salmon. We chose to examine these factors because previous studies have shown that emergence timing ( Beckman et al 2007) and growth during critical periods of the life cycle affects the proportion of males maturing at early ages relative to females (Rowe and Thorpe 1990a,b;Rowe et al 1991;Silverstein et al 1998;Shearer and Swanson 2000;Campbell et al 2003;Swanson et al , 2005Vøllestad et al, 2004;Shearer et al 2006). …”
Section: Introductionmentioning
confidence: 99%